Twin pregnancy among women with pregestational type 1 or type 2 diabetes mellitus. Issue 1 (5th April 2014) - González González, Nieves L.; González Dávila, Enrique; Goya, Maria; Vega, Begoña; Hernández Suarez, Mercedes; Bartha, Jose L.; ,
Abstract: Objective: To assess the impact of twin versus singleton pregnancy on obstetric and perinatal outcomes among women with pregestational diabetes mellitus (DM). Methods: Multicenter retrospective cohort study of women with pregestational DM and twin or singleton pregnancy, conducted in Spain during 2005–2010. Each group included 63 women (type 1 DM, n = 39; type 2 DM, n = 24). Results: Of 269 565 deliveries, 68 (0.025%) were twins of mothers with pregestational DM, with 28/63 (44.4%) conceptions achieved with assisted reproduction technology. Among women with type 1 DM, hypertensive complications were more common among those with twins than among controls (13% versus 3%, P = 0.02); the rate of preterm birth was higher (69% versus 15%, P < 0.001); and the rate of admission to the neonatal intensive care unit was higher (51% versus 21%, P = 0.005). Twin pregnancy was an independent risk factor for adverse perinatal outcomes regardless of the type of diabetes. Conclusion: Twin pregnancy in women with either type of DM dramatically increased the risk of perinatal morbidity. In mothers with type 1 DM, twin pregnancy was more often associated with hypertensive complications than singleton pregnancy. Transfer of more than one embryo should be avoided if ART is needed in a woman with DM.